Effects of green tea extract treatment on erythropoiesis and iron parameters in iron-overloaded β-thalassemic mice - Settakorn, Kornvipa; Kongkarnka, Sarawut; Chompupoung, Anchan; Svasti, Saovaros; Fucharoen, Suthat; Porter, John B.; Srichairatanakool, Somdet; Koonyosying, Pimpisid (Frontiers in Physiology, 2022)
β-Thalassemia is characterized by ineffective erythropoiesis leading to chronic anemia. Thus, increased iron absorption from the duodenum and via blood transfusions is required to maintain normal blood hemoglobin (Hb) levels and iron chelators in the removal of excessive iron. Certain agents are also needed for the improvement of stress erythropoiesis and iron dysregulation. Green tea extract (GTE), which is rich in epigallocatechin-3-gallate (EGCG), is known to possess radical scavenging and iron-chelating activities. We aimed to assess the effects of green tea extract on erythroid regulators, iron mobilization and anti–lipid peroxidation in the liver, spleen, and kidneys of iron-loaded β-globin gene knockout thalassemic (BKO) mice. Our results indicate that treatments of green tea extract and/or deferiprone (DFP) diminished levels of plasma erythropoietin (EPO) and erythroferrone (ERFE), and consistently suppressed kidney Epo and spleen Erfe mRNA expressions (p < .05) in iron- loaded BKO mice when compared with untreated mice. Coincidently, the treatments decreased plasma ferritin (Ft) levels, iron content levels in the liver (p < .05), spleen (p < .05), and kidney tissues of iron–loaded BKO mice. Furthermore, lipid-peroxidation products in the tissues and plasma were also decreased when compared with untreated mice. This is the first evidence of the orchestral role of green tea extract abundant with epigallocatechin-3-gallate in improving ineffective erythropoiesis, iron dysregulation and oxidative stress in iron-overloaded β-thalassemic mice.